2006
DOI: 10.1300/j013v43n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Prenatal Providers' Approaches to Four Different Risks: Alcohol, Tobacco, Drugs, and Domestic Violence

Abstract: A comparison of each risk across the Five A's illuminates the gaps between recommended and actual prevention methods and suggests directions for development of interventions and educational efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…113,133,[162][163][164][165][166][167][168] The synthesis identified that both the professional role of participants and the organisational context in which they worked could act as either barriers to or facilitators of an individual's ability to provide smoking cessation support to pregnant or postpartum women. Underpinning these factors was an acknowledgement that the association between maternal smoking and social disadvantage was a considerable barrier to addressing and supporting smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…113,133,[162][163][164][165][166][167][168] The synthesis identified that both the professional role of participants and the organisational context in which they worked could act as either barriers to or facilitators of an individual's ability to provide smoking cessation support to pregnant or postpartum women. Underpinning these factors was an acknowledgement that the association between maternal smoking and social disadvantage was a considerable barrier to addressing and supporting smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…There was also recognition in the review studies and interviews that HPs could take a more assertive position, drawing attention to the negative effects of smoking on the baby in pregnancy and regarding the risks of SHS after birth. 133,[162][163][164][165] The systematic review of HPs found that professionals recognised the importance of involving women's partners in smoking cessation advice but this type of engagement was described as difficult -perhaps more difficult in the review studies than in the experiences of partners and SOs interviewed for this study.…”
Section: Barriers From Partners and Significant Othersmentioning
confidence: 93%
“…In a qualitative study of prenatal care providers’ approaches to psychosocial risk factors, obstetricians felt “ill equipped” to manage issues related to domestic violence and other forms of abuse and “needed additional advice, tips and resources” to manage these patients. [18] In contrast, family medicine providers have a wider breadth of clinical training and may feel more equipped to handle a variety of psychosocial issues. In addition, almost 70% of obstetricians surveyed reported that less than 25% of their patients had at least one of the listed psychosocial risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[1517] This lack of intensive, risk-appropriate prenatal care services for many women with high psychosocial risk pregnancies may be due to provider level factors such as an underestimation of the prevalence of psychosocial risk factors, inadequate training, time constraints and a belief by providers that many interventions are ineffective. [18] Variation in approach towards psychosocial risk factors such as alcohol, tobacco and substance abuse during pregnancy has also been demonstrated among different types of prenatal care providers. [18]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation